Bergey's Manual of Systematics of Archaea and Bacteria 2020
DOI: 10.1002/9781118960608.gbm00513.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Methanothrix

Abstract: Me.tha'no.thrix. N.L. neut. n. methanum methane; Gr. fem. n. thrix , hair; N.L. fem. n. Methanothrix , methane (‐producing) hair. Halobacterota / Methanosarcinia / Methanotrichales / Methanotrichaceae / Methanothrix Straight, rod‐shaped cells with flat ends, usually 0.8–1.3 μm wide by 2.0–6.0 μm long enclosed in a tubular sheath. Forms short (∼5–25 μm) to long (>150 μm) flexible chains of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…This genus produces methane mainly from acetate, but it is also able to reduce CO 2 via direct interspecies electron transfer (DIET) with Geobacter spp. [ 61 , 62 ]. Members of Methanothrix are more frequently dominant in reservoirs from medium to high-temperature reservoirs [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…This genus produces methane mainly from acetate, but it is also able to reduce CO 2 via direct interspecies electron transfer (DIET) with Geobacter spp. [ 61 , 62 ]. Members of Methanothrix are more frequently dominant in reservoirs from medium to high-temperature reservoirs [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Synonyms: Methanosaeta harundinacea (Ma et al, 2006 ), Methanothrix harundinacea (Akinyemi et al, 2020 ).…”
Section: Description Of Methanocrinis Harundinaceus ...mentioning
confidence: 99%
“…The acetate-dependent methanogenesis is performed only by two genera– Methanosarcina and Methanothrix (formerly Methanosaeta ) (Boone et al, 2001 ; Akinyemi et al, 2020 ). Methanosarcina species are facultative acetotrophs with a low substrate affinity for acetate; many Methanosarcina spp.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that compare neonatal mortality by skilled birth attendants (SBA) and non-Skilled Birth Attendant (non-SBA) have suggested that the quality of the type of birth attendant is important for reducing the prevalence of neonatal mortality 5 , 6 . Other factors that have been found to be associated with neonatal mortality include age of woman 7 , 8 , place of residence 9 , 10 , marital status 11 , 12 , education and wealth 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%